(untitled) (Salam International Academic Journal, 2025)
Migration is a phenomenon that has posed serious challenges to many developing countries. Afghanistan, as one such country, has been affected by migration in various dimensions. This study aims to examine the consequences of migration, including its economic, educational, social, and cultural impacts, and to propose appropriate solutions for the people of Afghanistan. The research is applied in purpose and qualitative in nature. Data were collected through open-ended interviews, and the methodology used was Grounded Theory. The study population, selected through purposive sampling, consisted of 30 faculty members from Herat University and private universities in Herat Province. The data collection took place during the winter of 2024 (Solar Hijri year 1403). The findings indicate that migration brings both positive and negative consequences across economic, educational, social, and cultural dimensions for the Afghan population. The proposed solutions include: strategically guiding migration at the national level through comprehensive policymaking; utilizing migration as a driver of economic growth; offering education and vocational skills development; aligning educational curricula with labor market needs; creating favorable conditions to encourage reverse migration; strengthening social services; reinforcing social cohesion; promoting education and localization of diversity and pluralism; supporting migrants’ access to up-to-date education in host countries; providing assistance with language acquisition; ensuring positive psychological and social support for migrants; and encouraging their cultural and social participation. These measures can help reduce the negative consequences of migration for the Afghan people and call for practical and effective implementation.